An Assessment of Attitudes and Perceptions of Undergraduate IT Students on Mobile Information Literacy in Pakistan - Zahid, Amna (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The thesis has been conducted to assess the attitudes and perceptions of Undergraduate IT student in Pakistan regarding mobile information literacy in terms of their age, gender and year of study. Four sub-divisions form the basis of the study; Informationally Literate University, Informationally Literate Person, Framework of Information Literacy and ICT and Students. The study is quantitative in nature and makes use of survey questionnaire on Mobile Information Literacy (MIL) as the data collection tool. The sample size consists of five hundred registered bachelor students from IT department at Comsats University in Pakistan have contributed in the survey willingly. The method for data analysis used is descriptive and has been conducted using Arithmetic mean (X), Frequency (f), Percent (%), Post Hoc Test, Anova test and Independent T-test. Findings show positive perceptions of the students about mobile information literacy and no serious difference is seen between MIL as showed by age direction. Conversely, major difference is seen between the gender and year of study level of the students about MIL, which shows that a relationship exists between undergraduate IT students’ gender, year levels and MIL. The female students showed higher level perceptions regarding literacy of mobile information as compared to male students. The 1st year students showed high levels of perceptions for mobile learning while the 3rd year IT students showed the lowest level of perceptions towards mobile information literacy. Keywords: Student’s Attitude, Student’s Perceptions, Technology Literacy.

ÖZ: Bu çalışma, Pakistan'daki Bilişim Teknolojileri (BT) lisans öğrencilerinin Mobil Bilgi Okuryazarlığı (MBO) konusundaki tutum ve algılarının, üniversite içerisindeki bilgi okuryazarlığı alt bölümleri temelinde yaş, cinsiyet ve öğrenim yılı açısından değerlendirilmesini incelemek amacıyla yapılmıştır. Araştırma, kantitatif araştırma ve anket yöntemi kullanılarak yapılmış ve veri toplama aracı olarak kullanılan anket çalışması MBO üzerinedir, ve Pakistan Comsats Üniversitesi Bilgisayar Mühendisliği, Yazılım Mühendisliği ve BT Bölümlerine uygulanmıştır. Pakistan'daki Comsats Üniversitesi'nin BT ve Bilgisayar Mühendisliği ve Yazılım Mühendisliği bölümlerinden 500 kayıtlı lisans öğrencisi ankete gönüllü olarak katıldı. Toplanan veriler üzerinde Betimsel Analiz kullanıldı. Verilerin analizi Frekans (f), yüzde (%), Aritmetik ortalama (X), Tek Yönlü Anova kullanılarak ve T-testi yapılmıştır. Bulrgular, BT lisans öğrencilerinin çoğunluğunda MBO konusunda önemli ölçüde yüksek algı seviyeleri oluşturduğunu, yaş ve cinsiyet yönüne göre öğrenciler üzerinde ciddi bir fark oluşturmadığını gösterdi. Tersine, öğrencilerin öğrenim yılına göre mobil bilgi okuryazarlığı düzeyleri arasında büyük bir fark vardır; bu, lisans BT öğrencilerinin yıl seviyeleri ile mobil bilgi okuryazarlığı arasında, mobil öğrenmeye yönelik yüksek düzeyde algı gösteren 1. sınıf öğrencileri arasında bir ilişki olduğunu göstermektedir. 3. sınıf BT öğrencileri, mobil bilgi okuryazarlığı konusunda çok az bir algı seviyesi farkı gösterdiler. Anahtar Kelimeler: Öğrencinin Tutumu, Öğrencinin Algısı, Teknoloji Okuryazarlığı.
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technologies in Education, 2020. Co-Supervisor: Asst. Prof. Dr. Nilgün Suphi, Supervisor: Asst. Prof. Dr. Hasan Oylum.
Keywords: Computer and Instructional Technology Teacher Education; Information and Communication Technologies in Education; Education - Computer network resources; Distance Education; Computer Assisted Instruction; Educational Technology; Teaching - Computer network resources; Student’s Attitude; Student’s Perceptions; Technology Literacy; Technological Applications; ICT Technologies; Technological Literacy; Integrate Technology